Self-employment and life satisfaction among the elderly: Survey-based evidence from Sweden - Lina Aldén; Mats Hammarstedt (Research Institute of Industrial Economics (IFN), 2018)
This paper compares life satisfaction among the elderly (61 years of age or older) who are self-employed, wage-employed or out of the labour force in Sweden with the help of a unique survey. Sweden is interesting since the share of elderly, just as in other countries, has increased during the last decade. Encouraging the elderly to remain in the labour force is now high on the political agenda. We find that people who are self-employed report higher life satisfaction than people who are wage-employed or out of the labour force.General health is a strong determinant of life satisfaction but the differences among the groups remain when we control for health related variables. Further, the self-employed report higher job satisfaction than the wage-employed, and find their work less mentally straining or stressful. Even though our results are driven by different types of selection, we conclude that they underline the need for a flexible working life. Stimulating self-employment among older people may be an effective way to improve their life satisfaction, to increase Sweden's labour supply and to keep older people in the labour force.
Keywords: J14; J26; J28; 330; Self-employment; Ageing; Life satisfaction; Job satisfaction